Canaloplasty for the treatment of primary open-angle glaucoma: A protocol of systematic review and meta-analysis. Issue 22 (29th May 2020) - Sun, Peng; Liu, Hong-wei; Zhou, Ping-ping; Meng, Yan
Abstract: Background: Canaloplasty has been reported to manage primary open-angle glaucoma (POAG) effectively. However, no study has specifically and systematically investigated the efficacy and safety of canaloplasty for the treatment of POAG. Thus, this study will systematically and comprehensively appraise the efficacy and safety of canaloplasty for the treatment of POAG. Methods: MEDLINE, EMBASE, Cochrane Library, Web of Science, Cumulative Index to Nursing and Allied Health Literature, Allied and Complementary Medicine Database, Chinese Biomedical Literature Database, and China National Knowledge Infrastructure will be sought from the construction to the February 29, 2020. Only randomized controlled trials (RCTs) focusing on canaloplasty for the treatment of POAG will be included. Two reviewers will independently undertake selection of study, data extraction, and risk of bias assessment. Any doubts between 2 reviewers will be resolved through discussion with another experienced reviewer. RevMan 5.3 software will be employed for data analysis. Results: This study will summarize high-quality RCTs on investigating efficacy and safety of canaloplasty for the treatment of POAG. Conclusion: The findings of this study will help to determine whether canaloplasty is effective and safety for the treatment of POAG. Systematic review registration: INPLASY202040119.